Implementation of a Forward Chaining Expert System in Diagnosing Laptop Damage - Sakinah, Putri; Hendra, Yomei; Satria, Budy; Rahman, Zumardi; Maulana, Fajar; Syaputra, Aldo Eko (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Laptops have become a primary need for almost everyone, but the damage rate is also high. Manual diagnosis of laptop damage requires special expertise and is prone to errors that can exacerbate damage. The purpose of this study was to develop an expert system based on the forward chaining method to diagnose laptop damage. Data obtained through expert interviews, literature study, and the internet comprised 13 symptoms and five main types of laptop damage. Relate data in tables to form IF-THEN rules of the forward chaining method. The test results on six symptoms indicate that the system can diagnose IC Power damage with 100% accuracy, which is the highest diagnosis. In conclusion, the forward chaining method can diagnose laptop damage based on emerging symptoms.